The Effects of Therapy with Oestriol Succinate and Ethinyl Oestradiol on the Haemostatic Mechanism in Post-Menopausal Women - Davies, Terence; Fieldhouse, Gillian; McNicol, George P. (Thrombosis and Haemostasis, 1976)
The effects on the haemostatic mechanism of oestrogen therapy, given to prevent bone loss in post-menopausal women, have been investigated. Oestriol succinate was given orally to 10 women at a level of 2 mg/day for 1 month and for a further 3 months with incremental increase of 2 mg each month. 6 of the 10 women were subsequently treated with 25 μg/day orally of ethinyl oestradiol. Oestriol succinate therapy resulted in a small increase in the level of factor VII, a decrease in factor VIII concentration and increased sensitivity of platelets to aggregating agents. Ethinyl oestradiol treatment resulted in much more widespread changes with marked increases in coagulation factors VII, VIII, IX and X, decreased levels of antithrombin and dramatic increases in circulating plasminogen levels and euglobulin lysis activity. The data suggested that the nature of oestrogens employed therapeutically is important in determining the qualitative and quantitative effect of oestrogen therapy on components of the haemostatic mechanism.